Judicial Activism: Diantara Melindungi Supremasi Konstitusional Atau Transisi Menuju Juristocracy: Judicial Activism: Diantara Melindungi Supremasi Konstitusional Atau Transisi Menuju Juristocracy - Ni Luh Dewi Sundariwati (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
The Constitutional Court tends to choose to conduct judicial activism as a response to the inability of the law to realize the essence of substantive justice. This study aims to examine judicial activism in its position as a bulwark to protect the supremacy of the constitution or as a sign of the beginning of the transition to a juristocracy regime. The research method uses normative juridical research. The results showed that the Constitutional Court has the authority to test and even annul a law formed based on the will of the majority which is intended to ensure that the law formed based on the will of the majority does not ignore or limit the basic rights of individuals in their status as individuals or in their status as citizens. Judicial activism will provide protection for the supremacy of the constitution if it is carried out to expand the protection of the basic rights of vulnerable groups from actions or policies formed by the will of the majority. But on the other hand, judicial activism intersects with the vulnerability of the transition to juristocracy, which is characterized by increased court intervention to decide issues that are the domain of authority of other branches of state power.